2023
DOI: 10.5483/bmbrep.2022-0139
|View full text |Cite
|
Sign up to set email alerts
|

Particulate matter induces ferroptosis by accumulating iron and dysregulating the antioxidant system

Abstract: Particulate matter is an air pollutant composed of various components, and has adverse effects on the human body. Particulate matter is known to induce cell death by generating an imbalance in the antioxidant system; however, the underlying mechanism has not been elucidated. In the present study, we demonstrated the cytotoxic effects of the size and composition of particulate matter on small intestine cells. We found that particulate matter 2.5 (PM2.5) with extraction ion (EI) components (PM2.5 EI), is more cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 17 publications
1
10
0
Order By: Relevance
“…Excessive ROS stimulation can cause different types of cell death depending on its dose, duration, and characteristics of the organism. A previous study reported that PM causes ferroptosis [5], a type of cell death that is primarily dependent on intracellular iron overload and lipid peroxidation signaling and is characterized by ROS accumulation due to iron overload-related lipid peroxidation [6,7]. Our results demonstrated in ammasome activation and ferroptosis induced by PM, especially PM 2.5 that contains extraction ions; these cellular responses were inhibited through suppressed iron accumulation, lipid peroxidation, and ROS production.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Excessive ROS stimulation can cause different types of cell death depending on its dose, duration, and characteristics of the organism. A previous study reported that PM causes ferroptosis [5], a type of cell death that is primarily dependent on intracellular iron overload and lipid peroxidation signaling and is characterized by ROS accumulation due to iron overload-related lipid peroxidation [6,7]. Our results demonstrated in ammasome activation and ferroptosis induced by PM, especially PM 2.5 that contains extraction ions; these cellular responses were inhibited through suppressed iron accumulation, lipid peroxidation, and ROS production.…”
Section: Discussionsupporting
confidence: 51%
“…PM activates the in ammatory pathway through reactive oxygen species (ROS)-mediated mechanisms [3]. In addition, PM causes oxidative stress, lipid peroxidation, expression of in ammatory cytokine genes, and several types of cell death including ferroptosis [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Calu‐3 cells (2 × 10 6 cells/mouse) and 50% Matrigel (PBS/Matrigel, 1:1 v / v ; BD Biosciences) were mixed and subcutaneously transplanted into the right flank of 4‐week‐old female NRGA mice 21,22 . When the tumor size reached about 100 mm 3 , the mice ( n = 3, per group) were intratumorally injected with SARS‐CoV‐2 Delta (1 × 10 5 pfu/mouse).…”
Section: Methodsmentioning
confidence: 99%
“…For instance, Park et al demonstrated the cytotoxic effects of PM 2.5 on small intestine cells. 92 PM 2.5 with extraction ion (EI) components was found to be more cytotoxic than PM 2.5 containing only PAHs, and the cell death mechanism involved ferroptosis, as evidenced by iron overloading, ROS generation, and lipid peroxidation. Liproxstatin-1 and deferiprone attenuated the cytotoxicity induced by PM 2.5 EI.…”
Section: Airborne Particulate Matter (Pm)mentioning
confidence: 99%
“…Several studies have investigated the cytotoxic effects of PM and its association with ferroptosis in different cell types and organs. For instance, Park et al demonstrated the cytotoxic effects of PM 2.5 on small intestine cells . PM 2.5 with extraction ion (EI) components was found to be more cytotoxic than PM 2.5 containing only PAHs, and the cell death mechanism involved ferroptosis, as evidenced by iron overloading, ROS generation, and lipid peroxidation.…”
Section: Ferroptosis Inducers In Environmental Pollutantsmentioning
confidence: 99%